The Dimensions of Auditory Hallucination in Schizophrenia: Association with Depressive Symptoms and Quality of Life - V, Janaki; W, Suzaily; AR, Abdul Hamid; Z, Hazli; MN, Azmawati (IIUM Medical Journal Malaysia, 2017)
Introduction: Auditory hallucination (AH) is often unexplored in depth in clinical practice. This study sought to ascertain the relationship between AH, depressive symptoms and quality of life (QOL) and its association with socio-demographic and clinical variables. Methods: This was a cross sectional study done in a psychiatry unit involving 60 schizophrenic patients between 18 to 60 years old. Psychotic Symptom Rating Scale – Auditory Hallucination subscale (PSYRATS-AH), Calgary Depression Scale for Schizophrenia (CDSS) and World Health Organization Quality of Life-Brief scale (WHOQOL-BREF) were used as instruments. Results: Alcohol intake was found to be significantly associated with the severity of AH. A significant moderate positive correlation was found between AH total score and CDSS (r=0.53, p<0.001) and moderately high correlation between emotional characteristics subscale with CDSS (r=0.651, p<0.005). The PSYRATS-AH dimensions; amount of distress (r=0.721, p<0.001) and intensity of distress (r=0.757, p<0.001) showed significant high correlation with CDSS. As for QOL, frequency of AH (r=-0.419, p<0.01) and CDSS (r=0.435, p<0.01) showed significant moderate negative correlation, while duration, loudness, amount and intensity of distress, disruption to life and controllability of voices had significant fair correlation with QOL. Multiple regression analysis revealed that the frequency of AH (p=0.047), controllability of AH (p=0.027) and depressive symptoms (p=0.001) significantly predict QOL. Conclusion: Our results demonstrated that each dimension of AH had different contributions towards depressive symptoms and the QOL in patients with schizophrenia. Therefore, appropriate treatment focusing on the specific dimension of AH not only may reduce depressive symptoms, but may also improve QOL of these patients.